Leonard Bernstein : American original ; how a modern renaissance man transformed music and the world during his New York Philharmonic years, 1943-1976 /: American original ; how a modern renaissance man transformed music and the world during his New York Philharmonic years, 1943-1976. (2008) - Unknown
No abstract available